Populism, Islam, and the Quest for Utopia: Political Dynamics in 21st Century Europe - Pambudi, Kukuh Setyo (Journal for the study of religions and ideologies, 2025)
In the early 21st century, Europe has experienced a profound political transformation marked by the ascendance of populism, which emerges as a reaction to the multifaceted challenges posed by globalization, migration, and demographic changes. This paper explores the intricate interplay between populism and Islam within the context of contemporary European political dynamics, arguing that the rise of populist movements is not merely a manifestation of political discontent but a complex response to perceived existential threats to national identity and cultural integrity. By examining the narratives constructed by populist parties, this study highlights how these movements utilize Islam as a focal point for their utopian visions, often idealizing a return to a homogeneous national identity while simultaneously demonizing the "other." The analysis delves into the role of digital media in amplifying these narratives, creating echo chambers that reinforce radicalized political discourse and shape public perceptions of Islam. Ultimately, this paper contends that the convergence of populism and Islamophobia reflects deeper societal anxieties and underscores the urgent need for a critical examination of the implications for social cohesion and democratic values in Europe. Through a comprehensive review of relevant literature and case studies, this research contributes to the understanding of how populist ideologies are reshaping the political landscape and influencing the future of European integration.